Prophets, Profits and Protests: Prosperity Theology and Zimbabwean Gospel Music - Chitando, Ezra (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
While the phenomenon of prophets in Zimbabwe has attracted considerable media and scholarly interest, there has been less focus on responses towards prosperity theology, one of the direct products of the prophets, in music. In particular, gospel music has become one of the most strategic sites of contestation around prosperity theology. On the one hand, some artists celebrate prosperity as a mark of divine favour. On the other hand, there are artists who challenge the emphasis on material progress in Christianity. To address this gap in the extant literature, this chapter focuses on responses to prosperity theology in Zimbabwean gospel music, while integrating material from other genres of Zimbabwean music. The chapter culls the socio-economic and political context in which prophets who popularise prosperity theology have emerged. It proceeds to highlight the key tenets of prosperity theology. The chapter captures the celebration of prosperity theology in gospel music, as well as its contestation in the same. It also describes attitudes towards prosperity theology by artists in other musical genres. Overall, the chapter contends that the sharp divisions that have emerged towards prophets and prosperity theology are in turn played out in Zimbabwean music.
free